Significance of Sedimentological Studies on the Wisconsinan Stratigraphy of Southern Ontario - Sharpe, David; Barnett, Peter (Géographie physique et Quaternaire, 1985)
ABSTRACTDetailed facies mapping along Lake Erie and Lake Ontario Bluffs, plus other studies illustrate that sedimentological studies, especially those with geomorphic or landform control, have had three main effects on the Wisconsinan stratigraphy of Ontario: (1) improved understanding of depositional processes and environments of several major rock stratigraphic units, without altering the stratigraphic framework, (2) aided correlation of drift sequences, and (3) questioned previous interpretations and stratigraphic correlations of drift sequences. Thus sedimentological analysis can not be separated from stratigraphy because the interpretation of depositional environnments of many mapped strata relies on their geometry and the inclusion of regional data. The geomorphic control provided by sedimentological study of surface landforms is also important because assessment of older buried sediments such as those at the Scarborough Bluffs has been hampered by the failure to determine landform control. The Late Wisconsinan stratigraphy of Southern Ontario generally remains unchanged, except for questions on the role of climate versus ice margin dynamics. The pre-Late Wisconsinan stratigraphy is scarce and not well defined, yet sedimentary studies support the presence of glacial ice in the Ontario Lake basin for all of the Middle Wisconsinan and possibly earlier, including the formation of the Scarborough delta. Large channel cut and fill sequences in the Toronto area (Pottery Road Formation), initially interpreted as resulting from subaerial erosion, were probably formed by subaqueous or subglacial meltwater erosion. If so, the pre-Late Wisconsinan stratigraphy in southern Ontario changes because the Pottery Road Formation may not be an Early Wisconsinan correlative of the St. Pierre beds. The channel example illustrates that stratigraphie correlation without sedimentological investigations may be misleading.